Comparison of clinical features and outcomes of proliferative, fibrotic, and mixed subtypes of IgG4-related disease: A retrospective cohort study - Peng, Linyi; Zhang, Xinlu; Zhou, Jiaxin; Li, Jieqiong; Liu, Zheng; Lu, Hui; Peng, Yu; Fei, Yunyun; Zhao, Yan; Zeng, Xiaofeng; Zhang, Wen (Chinese medical journal, 2024)
Abstract Background: Immunoglobulin G4-related disease (IgG4-RD) is a recently recognized immune-mediated disorder that can affect almost any organ in the human body. IgG4-RD can be categorized into proliferative and fibrotic subtypes based on patients' clinicopathological characteristics. This study aimed to compare the clinical manifestations, laboratory findings, and treatment outcomes of IgG4-RD among different subtypes. Methods: We prospectively enrolled 622 patients with newly diagnosed IgG4-RD at Peking Union Medical College Hospital from March 2011 to August 2021. The patients were divided into three groups according to their clinicopathological characteristics: proliferative, fibrotic, and mixed subtypes. We compared demographic features, clinical manifestations, organ involvement, laboratory tests, and treatment agents across three subtypes. We then assessed the differences in treatment outcomes among 448 patients receiving glucocorticoids alone or in combination with immunosuppressants. Moreover, risk factors of relapse were revealed by applying the univariate and multivariate Cox regression analysis. Results: We classified the 622 patients into three groups consisting of 470 proliferative patients, 55 fibrotic patients, and 97 mixed patients, respectively. We found that gender distribution, age, disease duration, and frequency of allergy history were significantly different among subgroups. In terms of organ involvement, submandibular and lacrimal glands were frequently involved in the proliferative subtype, while retroperitoneum was the most commonly involved site in both fibrotic subtype and mixed subtype. The comparison of laboratory tests revealed that eosinophils (P = 0.010), total IgE (P = 0.006), high-sensitivity C-reactive protein (P <0.001), erythrocyte sedimentation rate (P <0.001), complement C4 (P <0.001), IgG (P = 0.001), IgG1 (P <0.001), IgG4 (P <0.001), and IgA (P <0.001), at baseline were significantly different among three subtypes. Compared with proliferative and mixed subtypes, the fibrotic subtype showed the lowest rate of relapse (log-rank P = 0.014). Conclusions: Our study revealed the differences in demographic characteristics, clinical manifestations, organ involvement, laboratory tests, treatment agents, and outcomes across proliferative, fibrotic, and mixed subtypes in the retrospective cohort study. Given significant differences in relapse-free survival among the three subtypes, treatment regimens, and follow-up frequency should be considered separately according to different subtypes.